Improvement of an Air Type Anti-Vibration Apparatus for Long-Period Earthquake Ground Motion - OGASAHARA, Takahito; WAKUI, Shinji (TRANSACTIONS OF THE JAPAN SOCIETY OF MECHANICAL ENGINEERS Series C, 2011)
In the precision measurement and positioning fields, e.g. the semiconductor exposure machine, an air type anti-vibration apparatus is generally implemented. The above machine must continuously operate because of a high price. However, when an earthquake occurs, the exposure machine must be suspended in order to avoid mechanical contact. In detail, when seismometer's measurement is beyond the determined value, the operation of anti-vibration apparatus is stopped for safety. Although such countermeasures against earthquake are installed, there are many reports such that the exposure machines suffer heavy damage from earthquakes. To overcome the above issue, several methods to avoid the mechanical contact caused by the earthquake are proposed. Firstly, a control model of air type anti-vibration apparatus with one degree-of-freedom and two type seismic waves for simulation are shown. Next, by using the changeover concerning floor vibration feedforward and/or feedback parameters, it is shown that the relative displacement between the floor and isolated table can be suppressed while the acceleration level on the isolated table becomes large. Finally, focusing the frequency responses, especially both the transmissibility x/x0 and (x-x0)/x0 in low frequency region, where x and x0 mean the isolated table and the floor displacements respectively, the justification for both the suppression of relative displacement and the increase of acceleration level are explained.